PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 166 PEKANBARU - Delmita '; Syahrilfuddin '; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the low learning outcomes Elementary School third grade students 166 Pekanbaru. This research aims to improve mathematics learning outcomes Elementary School third grade students Pekanbaru 166 Academic Year 2014/2015 through Cooperative Learning Model Application Type Make A Match. The subjects were students of class III Elementary School 166 Pekanbaru the number of students as many as 35 people, consisting of 17 male students and 18 female students. This research is a classroom action research that consists of 2 cycles. I cycle consists of 2 meetings with one daily replications, in cycle II consists of 2 meetings with 1 time daily tests. Of the 35 students only as many as 11 students (31.42%) that received a daily test scores above or equal to the minimum completeness criteria (KKM). While as many as 24 students (68.57%) is still below the KKM. After the action on the first cycle as many as 20 students (57.14%) scored above the daily tests or equal to KKM KKM, in cycle II as many as 30 students (85.71%) who received grades above daily tests KKM , Activity of students during the learning process the first cycle an average of 60% with enough categories, and Cycle II average of 81% categorized Good. The data of this study indicate that the learning outcomes of students has increased, before action is taken on average amounted to 68.28 student learning outcomes. In the first cycle amounted to 71.00 increased 2.72 points, on the second cycle amounts to 84.00 increased 13.00 points. From the results of this study concluded that through the Cooperative Learning Model Application Type Make A Match to Improve Learning Outcomes Math Grade III Elementary School 166 Pekanbaru.Keywords : Cooperative Learning Model Application Type Make A Match, Math Learning Outcomes